Phosphorus metabolites in the human placenta estimated in vivo by magnetic resonance spectroscopy. Issue 7 (July 1991) - Weindling, A M; Griffiths, R D; Garden, A S; Martin, P A; Edwards, R H
Abstract : Normal human placental metabolism has been studied in vivo by image localised 31P magnetic resonance spectroscopy in 13 women with anterior placentas; five, however, were too fat for useful spectral signals to be obtained. Magnetic resonance spectra of good quality which were considered to have arisen from the placenta were obtained from seven women with uncomplicated pregnancies (median gestational age 35 weeks, range 28-39). One other woman had a twin pregnancy in which one fetus had died a few days before. The phosphodiester signal from the placenta of the dead fetus was outside the 95% confidence intervals for normal placentas, suggesting that this technique may potentially be useful in the assessment of placental function.